Internal Microstructural Changes and Stress Evolution in Silicon Nanoparticle Based Composite Electrodes. Issue 14 (8th December 2017) - Kumar, Ravi; Woo, Jae Ha; Xiao, Xingcheng; Sheldon, Brian W.
Abstract : In battery electrodes, the high lithium capacity of silicon is accompanied by large volume changes that can lead to substantial microstructural changes inside of particle based electrodes. Stresses that develop as these changes take place were monitored directly with in situ curvature measurements. The silicon loading was varied and results with two different binders were compared (sodium Alginate and carboxymethyl cellulose (CMC)). In reference carbon black electrodes with 0% Si, the compressive stress increases linearly and is largely reversible and elastic during delithiation. In contrast the Si-containing electrodes exhibit a stress response with significant hysteresis that is characteristic of plastic flow. The stiffer Na-Alginate binder also leads to higher stresses than the CMC, in electrodes with otherwise similar compositions. This implies that the stress magnitude is directly related to the binder elastic modulus. Ex situ imaging along with in situ dilatometer measurements indicate that thickness changes are minimal in the elastic regime, while a large thickness increase coincides with the transition to plastic flow. This implies that internal particle rearrangement accommodates the large volume changes in the silicon. Simple cell models with periodic particle arrays were also employed to provide basic insight into the internal changes that occur during cycling.